2018
DOI: 10.1021/acsphotonics.8b00494
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Upconversion Luminescence Emission of Rare Earth Nanophosphors in Aqueous Solution with Thousands Fold Enhancement Factor by Low Refractive Index Resonant Waveguide Grating

Abstract: The enhancement of upconversion luminescence (UCL) of rare earth doped upconversion nanoparticles (UCNPs) in aqueous solution is particularly important and urgently required for a broad range of biomedical applications. Herein, an effective approach to achieve highly enhanced UCL from NaYF4:Yb3+,Tm3+ UCNPs in aqueous solution is presented. We demonstrate that UCL of these UCNPs can be enhanced more than 104-fold by using a mesoporous silica low refractive index resonant waveguide grating (low-n RWG) in contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
16
0
1
Order By: Relevance
“…Although the local field enhancement provided by dielectric nanostructures is typically smaller than that of plasmonic nanostructures, dielectric nanostructures do not suffer parasitic energy losses manifested by fluorescence quench caused by the metal's electron gas through its many internal degrees of freedom (Joule losses). Through proper design of the structure, some dielectric nanostructures can enhance the UCL of UCNPs more than 100 times [28,[41][42][43][44][45][46][47]. A variety of dielectric nanostructures, such as photonic crystals [28,[41][42][43][44], and metasurfaces [45][46][47] have been employed to enhance the UCL of UCNPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the local field enhancement provided by dielectric nanostructures is typically smaller than that of plasmonic nanostructures, dielectric nanostructures do not suffer parasitic energy losses manifested by fluorescence quench caused by the metal's electron gas through its many internal degrees of freedom (Joule losses). Through proper design of the structure, some dielectric nanostructures can enhance the UCL of UCNPs more than 100 times [28,[41][42][43][44][45][46][47]. A variety of dielectric nanostructures, such as photonic crystals [28,[41][42][43][44], and metasurfaces [45][46][47] have been employed to enhance the UCL of UCNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Through proper design of the structure, some dielectric nanostructures can enhance the UCL of UCNPs more than 100 times [28,[41][42][43][44][45][46][47]. A variety of dielectric nanostructures, such as photonic crystals [28,[41][42][43][44], and metasurfaces [45][46][47] have been employed to enhance the UCL of UCNPs. Recently, we demonstrated that the UCL of UCNPs can be enhanced more than 1000-fold by depositing UCNPs atop a resonant waveguide grating (RWG) structure, also termed 1D photonic crystal substrate, thanks to its guided mode resonance (GMR) to promote the local field of the excitation light atop the RWG [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…The monodisperse hexagonal-phase (β-phase)_ NaYF 4 :Yb 3+ ,Er 3+ nanocrystals were synthesized through a thermal decomposition process as our previous study [40]. The typical procedure is as follows: 0.78 mmol of YCl 3 , 0.2 mmol of YbCl 3 , 0.02 mmol of ErCl 3 were mixed with 6 mL of OA and 15 mL of ODE into a 100 mL three-necked flask.…”
Section: Synthesis Of Hydrophobic Ucnp-oamentioning
confidence: 99%
“…The PAA-modified NaYF 4 :Yb 3+ ,Er 3+ UCNPs (UCNP-PAA) were prepared by using a modified ligand exchange strategy [40,41]. A typical procedure is as follows: the mixture containing 1 mL of PAA solution in ethanol (~1 wt%) and 0.5 mL of UCNP-OA dispersed in chloroform (~1 wt%) was stirred vigorously for at least 12 h at room temperature.…”
Section: Synthesis Of Hydrophilic Ucnp-paamentioning
confidence: 99%
“…Diblock copolymers can display different self-assembly behaviors, including lamellar, gyroid, cylinder, and spherical nanostructures, which possess several potential applications in drug delivery, photonic crystals, and nanotechnology [ 1 , 2 , 3 , 4 ]. However, mediating the different molecular weights of each block segment to control the volume fraction by using living polymerization methods may be time-consuming and difficult and thus blending the homopolymer or another block copolymer through intermolecular hydrogen bonding interactions has received much interest recently [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%